2020
DOI: 10.1111/1759-7714.13381
|View full text |Cite
|
Sign up to set email alerts
|

Does surgically resected small‐cell lung cancer without lymph node involvement benefit from prophylactic cranial irradiation?

Abstract: Background It has previously been demonstrated that surgically resected small‐cell lung cancer (SCLC) patients could benefit from prophylactic cranial irradiation (PCI). However, PCI in patients without lymph node involvement remains controversial. This study includes a larger sample size to evaluate the benefit of PCI therapy in this specific population. Methods The records of surgically resected SCLC patients without lymph node involvement (N0M0) in Shanghai Chest Hospital were retrospectively reviewed. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Due to the paucity of cases undergoing surgery, the effect of PCI on SCLC patients who underwent surgical resection for the primary tumor remains unclear. We and other groups have shown that PCI could improve OS and decrease BM in SCLC patients with p-II/III stage, but not p-I stage, which is likely due to the low incidence of BM in patients with p-I stage (16)(17)(18)24). Specifically, recent data from our center showed that of the 146 surgically resected SCLC patients without lymph node involvement (pN0), only 11.6% (17/146) of patients developed BM, and PCI does not reduce the risk of cerebral recurrence of resected pT1-2N0M0 SCLC (17).…”
Section: The Role Of Pci In Early-stage Sclc After Surgerymentioning
confidence: 72%
See 2 more Smart Citations
“…Due to the paucity of cases undergoing surgery, the effect of PCI on SCLC patients who underwent surgical resection for the primary tumor remains unclear. We and other groups have shown that PCI could improve OS and decrease BM in SCLC patients with p-II/III stage, but not p-I stage, which is likely due to the low incidence of BM in patients with p-I stage (16)(17)(18)24). Specifically, recent data from our center showed that of the 146 surgically resected SCLC patients without lymph node involvement (pN0), only 11.6% (17/146) of patients developed BM, and PCI does not reduce the risk of cerebral recurrence of resected pT1-2N0M0 SCLC (17).…”
Section: The Role Of Pci In Early-stage Sclc After Surgerymentioning
confidence: 72%
“…This survival benefit was evident from PSM-based univariate and multivariate Cox analyses. In general, pN0 belongs to the p-I stage that associates with a low incidence of BM (16)(17)(18)24), which could explain the unbeneficial role of PCI treatment in this subgroup. Additionally, we observed that PCI was not superior to the non-PCI group in patients with pN2, which predominantly belongs to p-stage III.…”
Section: The Role Of Pci In Advanced-stage Sclc With Lymph Node Metastasis After Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, only manuscrpits dealing directly with surgical pulmonary resection in SCLC were selected. Based on these criteria, 14 publications were identified and included in the review [8][9][10][11][12][13][14][15][16][17][18][19][20][21](Tab. 1).…”
Section: Review Methodsmentioning
confidence: 99%
“…The role of pulmonary resection in early SCLC has been controversial for many decades [6]. Undoubtedly, it constitutes a valuable component of a combined modality treatment, especially in the situation when a small peripheral lesion detected at low-dose computed tomography (LDCT) is re-sected, and after the resection the diagnosis of SCLC is established [9,10]. However, many lung physicians do not refer patients with small peripheral pulmonary lesions for thoracic surgical resection when SCLC is suspected, but prefer observation.…”
Section: Description Of the State Of Knowledgementioning
confidence: 99%